New species of Boreofairchildia Wagner & Stuckenberg, 2016 (Diptera: Psychodidae) from Brazil - Freddy Bravo (EntomoBrasilis)
Boreofairchildia Wagner & Stuckenberg, 2016 (Diptera: Psychodidae) currently includes fourteen acknowledged species. This genus is mainly found in the Neotropical region, although one species has been described from the Nearctic area. Two species are known Brazil, both from the state of Espirito Santo. In this paper, a new species from the Atlantic Forest of Espirito Santo is described, increasing the total number of Brazilian species to three and the overall species count in the genus to fifteen.